Hubungan Antara Optimisme dengan Produktivitas Kerja Pada Driver Jeggboy&Girl Salatiga - Nelvara, Elva; Kusumiati, Ratriana Yuliastuti Endang (Innovative: Journal Of Social Science Research, 2024)
In today's developing era, transportation facilities have also developed in the community. In Indonesia, there are many transportation facilities used, one of which is ojek which is now also developing with online motorcycle taxis, ojek transportation is in great demand by the public because it is easily accessible. The purpose of this study was to determine the relationship between optimism and work productivity experienced by Jeggboy &girl Salatiga drivers. This research uses quantitative methods by involving numbers and analytical techniques that use statistics. Sample determination in this study used purposive sampling technique. A total of 51 drivers (male = 37; female = 14) at PT Jeggboy & girl Salatiga were sampled in this study. The measuring instrument used in the study is the Likert Scale. From the results of a simple linear regression analysis, a value of p = 0.000 (p<0.05) is obtained. These results show that optimism has a positive and significant effect on work productivity. The findings also showed that the level of optimism of jeggboy drivers was at a moderate level. Keywords: optimism, work productivity, online motorcycle taxis.